The Influence of Interior Design and Service Quality on Interest in Revisiting Café Arabica, Central Park Mall - Kusumaningrum, Dewi; Wijaya, Cindy (International Journal of Travel, Hospitality and Events, 2024)
Purpose : this research aims to determine the influence of interior design and service quality on interest in returning to Cafe Arabica Central Park Mall. Research Methods : this research is a type of quantitative research and uses a questionnaire as a data collection technique. The sample used was 80 people selected using purposive sampling technique. The analytical method used is Multiple Linear Regression Analysis, T Test, and F Test. Results and discussion : The results of this study show that there is a significant partial or individual influence between interior design variables and service quality on interest in returning visits. Apart from that, it can also be seen that there is a significant influence between interior design variables and service quality simultaneously on interest in returning to visit. Interior design is related to creating a room or shop atmosphere that can influence and create an image in the mind of a visitor that influences the buyer's emotions, and generates or influences interest in visiting. In addition, the level of visitor satisfaction depends on the quality of service. Service companies really depend on service quality because it will influence visiting interest. Implication : It is hoped that the contents of this research for the Arabica Central Park Mall Cafe can become a reference for assessing consumers' interest in returning to the cafe and also become an input for improving the quality of service and implementing better types of design as time goes by in order to increase the level of interest in returning to visit. towards Arabica Cafe Central Park Mall.